Potensi Penurunan Produksi Padi Akibat Variabilitas Curah Hujan di Kabupaten Subang Jawa Barat - Ruminta Roem; Agus Wahyudin; Tati Nurmala; Joko Wiratmo; dan Fiky Yulianto Wicaksono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Research on hazard, vulnerability, and risks of the decline in rice production due to climate change has been implemented in Subang West Java. This study aims to assess the level of hazard, vulnerability, and risks of the decline in rice production and identify areas that very high level of the decline in rice production. Materials of this study is data of climate, agroclimate, rice production, and socio-economic. Methods of this study is descriptive explanatory that using risk assessment concept where risk is a function of hazard and vulnerability. The results was showed in spatial map using GIS. The results indicate that in Subang area has experienced climate change shown by the changing patterns (trend) of rainfall, rain day, and the distribution of annual rainfall. Decreased rice harvested area above 5.2% per year occurred in Cisalak, Dawuan, Pabuaran, Patokbesi, Pagaden, and Pusakanagara. Decreased rice production over 11.2% per yeas occurred in Cisalak, Dawuan, Pabuaran, and Pusakanagara.The very high vulnerability occurred in Pabuaran.The high risks of decline in harvested area and production of rice respectively found in Patokbesi and Pabuaran. The high risk reduction in harvested area and production of rice in the region due to the disruption of water supply, growth, development, and production plants due to climate change.